2009
DOI: 10.2196/jmir.1152
|View full text |Cite
|
Sign up to set email alerts
|

Health Professionals’ Attitudes Towards Using a Web 2.0 Portal for Child and Adolescent Diabetes Care: Qualitative Study

Abstract: Background The Internet, created and maintained in part by third-party apomediation, has become a dynamic resource for living with a chronic disease. Modern management of type 1 diabetes requires continuous support and problem-based learning, but few pediatric clinics offer Web 2.0 resources to patients as part of routine diabetes care.Objectives To explore pediatric practitioners’ attitudes towards the introduction of a local Web portal for providing young type 1 diabetes patients with interactive pedagogic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
121
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(129 citation statements)
references
References 35 publications
(49 reference statements)
6
121
0
2
Order By: Relevance
“…The topics covered in the selected studies were as follows: two studies address the use of a tool to assess websites (23)(24) ; six address the development, use, evaluation, and/or application of software for computers and smartphones (14, 16-17, 19, 21-22) ; two deal with the attitude and behaviour of health professionals and parents of children and adolescents when accessing online portals (18,20) ; one paper compares the effectiveness of direct access to an online platform with regard to the consultation of health workers (15) ; and another demonstrates how the characteristics of parents influence searches of health information online (13) . The analysis of the selected studies revealed positive and negative aspects of the use of online information for the families of children and adolescents with chronic illness, which resulted in two categories: Potentialities of the use of online information for the families of children and adolescents with chronic illness, and Weaknesses of the use of online information for the families of children and adolescents with chronic illness.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The topics covered in the selected studies were as follows: two studies address the use of a tool to assess websites (23)(24) ; six address the development, use, evaluation, and/or application of software for computers and smartphones (14, 16-17, 19, 21-22) ; two deal with the attitude and behaviour of health professionals and parents of children and adolescents when accessing online portals (18,20) ; one paper compares the effectiveness of direct access to an online platform with regard to the consultation of health workers (15) ; and another demonstrates how the characteristics of parents influence searches of health information online (13) . The analysis of the selected studies revealed positive and negative aspects of the use of online information for the families of children and adolescents with chronic illness, which resulted in two categories: Potentialities of the use of online information for the families of children and adolescents with chronic illness, and Weaknesses of the use of online information for the families of children and adolescents with chronic illness.…”
Section: Resultsmentioning
confidence: 99%
“…Chart 1 -Characterisation of the papers included in the review (continue) In the first category, the potentialities of the use of online information to support children and youths with chronic disease were: search for online information, both sexes, in families with chronically ill children, which serves as relief for the parents since they verified that the symptoms and behaviours of their children are appropriate for the age and provide knowledge for the family members to discuss treatment with the physician (13) ; source of complementary knowledge (17) ; supports caregivers due to the dynamism, flow, and possibility of exchanging information (18,20) ; helps parents cope with chronic diseases (14,16,(19)(20)(21)(22) ; attracts teenage audiences (16) ; contributes in self-care (17)(18) ; has positive results in online therapeutic follow-up, as in the consultations at the doctors' offices (15) ; and although the internet is widely accessed, health professionals continue to be the main source of information (20) . In the second category, the weaknesses of the use of online information to support the parents of children and adolescents with chronic diseases were: difficulties in understanding the information (14,19) ; the "digital divide" (limited knowledge of different languages, use of high-cost electronic devices, and access for the low-income population) (16,(19)(20)(21) ; restriction of online therapeutic models to populations in specific chronic conditions (15) ; low quality (23)(24) and reliability (24) of the available content; low availability of data for adolescents (23) ; deficit of skills of health professionals to identify and conduct the use of online support tools (20)(21)(22)(23)(24) , and ignorance of legal regulations on online communication …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its success has given rise to the medical "Web 2.0", with initiatives like a medical collaborative encyclopedia [1], various focused medical conferences such as Medicine 2.0 [2], special issues of scientific journals [3], focused medical informatics, and medically-related social groups [4].…”
Section: Introductionmentioning
confidence: 99%